Rancang Bangun Alat Pengering Ikan Asin Otomatis Berbasis Arduino Uno - Moh Farid Lukman; Samsul Arifin; Mufidatul Islamiyah (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2022)
The coastal area of ​​Rembang Regency carries out drying of salted fish in a conventional way with a drying area in the form of a rack or board arranged on open land. However, this method has a weakness because the drying process still requires more time, namely 1 day to dry the anchovy and 2 days to dry the kite. If the weather is cloudy and it rains lightening takes 3 to 5 days. The working principle of the design of the Arduino Uno-based salted fish drying device is to use a heating element as an automatic drying room heater, and a fan as a stabilizer for air circulation, then the LM35 temperature sensor to find out what the temperature is in the drying rack, 16x2 LCD which functions to display the temperature value, menu, and drying time, then Arduino Uno as a microcontroller programmed to run the system. The design of this tool has a size of 35cm, width 30cm, and length 40cm, and has 2 pans for drying fish, each of which can only accommodate fish weighing `1/4kg. The overall test results were carried out by drying 2 types of fish, namely scad and anchovies weighing 1/2 kg and 1/4 kg.